2006
DOI: 10.1074/jbc.m513465200
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTS1 Interacts with, Cleaves, and Modifies the Extracellular Location of the Matrix Inhibitor Tissue Factor Pathway Inhibitor-2

Abstract: ADAMTS1 is an extracellular metalloproteinase known to participate in a variety of biological processes that includes inflammation, angiogenesis, and development of the urogenital system. Many of its functions rely on its catalytic activity, which thus far has been limited to the cleavage of the matrix proteoglycans aggrecan and versican. However, it is likely that other substrates exist. Using a yeast two-hybrid screen, we identified the Kunitz-type inhibitor, tissue factor pathway inhibitor-2 (TFPI-2), as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 52 publications
2
36
0
Order By: Relevance
“…Finally, tissue factor pathway inhibitor (TFPI) is a matrixassociated serine proteinase inhibitor consisting of three tandem Kunitz-type domains (K1, Asp13-Arg78; K2, Glu92-Gly150; and K3, Glu182-Lys241) [74]. There is a nonuniform charge distribution (a positively charged C-terminal tail) within the molecule [75][76][77].…”
Section: Tissue Factor Pathway Inhibitor (Tfpi)mentioning
confidence: 99%
“…Finally, tissue factor pathway inhibitor (TFPI) is a matrixassociated serine proteinase inhibitor consisting of three tandem Kunitz-type domains (K1, Asp13-Arg78; K2, Glu92-Gly150; and K3, Glu182-Lys241) [74]. There is a nonuniform charge distribution (a positively charged C-terminal tail) within the molecule [75][76][77].…”
Section: Tissue Factor Pathway Inhibitor (Tfpi)mentioning
confidence: 99%
“…ADAMTS-1 can cleave and remodel components of the extracellular matrix, and it has antiangiogenic properties. [29][30][31] Compared with normal hepatocytes, the expression of ADAMTS-1 was markedly decreased in PLC/PRF-5 cells. Furthermore, incubation with 10 lM 17-AAG resulted in a 1.88 (95% CI, 1.31-2.45)-fold increase in ADAMTS1 mRNA after 24 hours, confirming that 17-AAG can revert gene expression associated with vascular invasion.…”
Section: Itga7mentioning
confidence: 99%
“…ADAMTS1 substrates described to date include the proteoglycans aggrecan (15), versican (16), nidogens-1 and -2 (17), thrombospondin-1 (10), syndecan-4 (18), and TFPI2 (19). It has been recently shown that ADAMTS1 induces a stromal reaction in vivo through the recruitment of fibroblastic cells (20).…”
mentioning
confidence: 99%